A CAD environment for the fast computation of Added Masses. (15th September 2017) - Ceruti, A.; Bombardi, T.; Marzocca, P.
Abstract: This paper describes the features of AMCOMP, a CAD environment conceived to manage the computation of the Added Masses of bodies moving in an infinite fluid. A methodology already published in literature has been implemented in a CAD environment and its features are exploited to perform the evaluation of the Added Masses. These include the importing of the model in STL file format and the computation of the complete Added Mass matrix and non-dimensional terms. The CAD has been validated by computing the Added Masses values of bodies whose exact formulation was found in literature. The validated tool has been applied to more complex case studies where the Added Masses values were guessed using empirical laws or the equivalent ellipsoid approximation. Significant differences have been found between approximated methods and computations on real shapes. It is shown that the precision in the Added Masses computation and the computational time depend on the meshing quality of the model and power of the PC on which the software runs. Several tools have been merged to obtain a model useful for the Added Masses computation and to assess the errors arising from using approximated formulas instead of the real shape of the body. Highlights: An accurate Added Masses estimation is required to model the dynamics of marine vehicles. Simplified methods available in literature could lead to significant errors in the Added Masses prediction. There are no available tools to rapidly compute Added Masses coefficients. A user-friendly CAD tool to rapidly and accurately compute Added Masses is proposed.